information and communication technology and mechanisms to improve public service in the local administration -the municipality as a model- - Ammaria, abdelhakim; sebti, rachida (Journal of Social Sciences and Humanities, 2021)
The public institutions, including the local administration, has seen greet acceleration in recent years in the application of ICTs, which has led to a total transformation in work, espesially in the quality of services provided to citizens, since the government has for years made a new programme in the telecomminications sector called « E-ALGERIA », in an attempt to generalize the use of various modern technologies in various department and institution. This project will allow the increase the efficiency of the algerian public administration and its transformation into a modern electronic management based on information and communication technology resources, to provide its services to citizens effeciently, consequently, this stady aims to know the mechanisms and measures taken and applied on the ground to improve public service in local administration, especially municipalities, and highlight the challenges they face in light of technological developement, the digital transformation witnessed by the local administratio, which is considered the most effective way to improve the service provided to the citizen as well as modernizing the local administration in all respects in light of the digital environment as an imperative and a necessity.